Pollen wall degradation in the Brassicaceae permits cell emergence after pollination. Issue 8 (22nd August 2017) - Edlund, Anna F.; Olsen, Katrina; Mendoza, Christian; Wang, Jing; Buckley, Trudyann; Nguyen, Mai; Callahan, Brooke; Owen, Heather A.
Abstract : PREMISE OF THE STUDY: Despite attempts to degrade the sporopollenin in pollen walls, this material has withstood a hundred years of experimental treatments and thousands of years of environmental attack in insects and soil. We present evidence that sporopollenin, nonetheless, locally degrades only minutes after pollination in Arabidopsis thaliana flowers, and describe here a two‐part pollen germination mechanism in A. thaliana involving both chemical weakening of the exine wall and swelling of the underlying intine. METHODS: We explored naturally occurring components from pollen and stigma surfaces and found a tripartite mix of hydrogen peroxide, peroxidase and catalase enzymes (all at high levels at the pollination interface) to be experimentally sufficient to degrade the sporopollenin of some Brassicaceae family members. KEY RESULTS: At pollination, factors carried on the pollen surface may mix with factors on the stigma surface in a reaction that locally oxidizes the exine pollen wall. Hydrogen peroxide, catalases, and peroxidases are biologically present at the right time and place and, when mixed experimentally, are sufficient to degrade the walls of susceptible pollen. CONCLUSIONS: Our work on native biochemistry for breaching sporopollenin suggests new research directions in pollen aperture evolution and could aid efforts to analyze sporopollenin's composition, needed for application of this corrosion‐resistant, but long‐intractable material.